A Mobile Triaxial Stabilized Ship-Borne Radiometric System for In Situ Measurements: Case Study of Sentinel-3 OLCI Validation in Highly Turbid Waters - Haoran Jiang; Peng Zhang; Hong Guan; Yongchao Zhao (Remote Sensing)
This study presents the “Mobile Triaxial Stabilized Water-leaving Reflectance Measurement System” (MTS-WRMS), a ship-borne radiometric system designed for high-precision acquisition of water-leaving radiance (Lw) and remote sensing reflectance (Rrs) in mobile aquatic environments. The system employs a triaxial stabilized gimbal to maintain the orientation of three spectrometers, effectively mitigating angular deviations. The system also features automatic azimuth adjustment to maintain the relative sun-sensor azimuth angle within the optimal range of 90° ≤ φ ≤ 135° and supports long-range wireless telemetry for autonomous real-time monitoring. The system’s accuracy was validated through the “direct approach” experiments, which demonstrated low systematic bias, with a mean weighted absolute percentage deviation (WAPD) of 4.42% in the 440–720 nm range, which covers 90% of radiant energy. Additionally, ground validation involving 296 matched spectra from Gaoyou and Zhuhai revealed that Sentinel-3 A/B OLCI products tend to overestimate Rrs in highly turbid waters, with weighted percentage deviation (WPD) and WAPD values of about 16% and 31%, respectively. The overestimation was particularly pronounced in the 400–443 nm range, likely due to low Rrs and inadequate atmospheric correction. The MTS-WRMS provides an advanced tool for accurate, real-time Rrs measurements, offering valuable insights into temporal and spatial variations in water bodies.